Orientation To Happiness Among Senior Secondary School Students Of Hilly Areas - et. al., Dr. Nimisha Beri, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
There are many ways to live happy but positive psychology revolves around three possible pathways: Pleasureful life, meaningful life and engaged life. Fredickson (1998, 2000) suggested that pleasure that is related to positive emotions is prerequisite for curiosity and learning and it is directly converted to physical, intellectual and social wellbeing. Meaning is another factor to improve happiness and wellbeing in different origin. Engaged life is based on activities in which individual is in a state of flow. People who pursue three orientations to happiness live full life and full life leads to life satisfaction, engagement and meaning and promote the development of wellbeing. Therefore, this study was conducted with an objective to explore the level of different types of orientation to happiness among senior secondary school students and find differences with resect to gender and type of school. Following findings have been drawn from the analysis of the study that Female senior secondary school and students from private senior secondary schools students reported higher orientation to happiness as compare to counterpart students.